Miocene Evolution of North Atlantic Sea Surface Temperature. Issue 5 (17th May 2020) - Super, James R.; Thomas, Ellen; Pagani, Mark; Huber, Matthew; O'Brien, Charlotte L.; Hull, Pincelli M.
Abstract: We reconstruct sea surface temperatures (SSTs) at Deep Sea Drilling Project Site 608 (42.836°N, 23.087°), north of the Azores Front, and Ocean Drilling Program Site 982 (57.516°N, 15.866°), under the North Atlantic Current, in order to track Miocene (23.1–5.3 Ma) development of North Atlantic surface waters. Mean annual SSTs from TEX86 and U K′ 37 proxy estimates at both sites were 10–15 °C higher than modern through the Miocene Climatic Optimum (17–14.5 Ma). During the global cooling of the Middle Miocene Climate Transition (~14.5–12.5 Ma), SSTs at midlatitude Site 608 cooled by ~6 °C, whereas high‐latitude Site 982 cooled by only ~2 °C, resulting in an ~4 Myr collapse of the SST gradient between the two sites. This regional pattern is inconsistent with an increased latitudinal surface temperature gradient, as generally associated with global cooling episodes linked to decreasing p CO2 levels. Instead, the pattern is best explained by enhanced ocean heat transport into the high‐latitude North Atlantic superimposed on the global cooling trend, probably due to enhanced Atlantic meridional overturning circulation and/or a stronger North Atlantic Current. During global late Miocene cooling (~8–7 Ma), surface waters cooled by ~6 °C at Site 982 while minimal change occurred at Site 608, reestablishing the North Atlantic SST gradient. The collapse and reemergence of the SST gradient between the middle‐ and high‐latitude North Atlantic suggests that interaction between changes in regional ocean circulation and the global response to changes in greenhouse gas concentration was important in Miocene climate evolution. Key Points: Biomarker estimated North Atlantic sea surface temperature was 10–15 °C warmer than modern during Miocene Climatic Optimum (17–14.5 Ma) Surface temperature gradient from middle‐ to high‐latitude North Atlantic collapsed for ~4 Myr following global cooling starting at ~14.5 Ma Ocean heat transport to the high‐latitude North Atlantic increased at ~14 Ma, likely due to oceanic gateway or ocean circulation changes